Endoscopic Submucosal Dissection of the Angiolipoma at Hypopharynx-Esophageal Introitus. (14th February 2020) - Liu, Lu; Miao, Feng; Guo, Hai-Mei; Li, Nuo; Jiao, Shu-Hua; Cai, Shuang; Liu, Peng-Liang; Zhang, Shan-Shan; Ma, Jia; Weng, Yang; Sun, Ying; Tang, Yin-Si; et al.
Abstract : Angiolipoma in the region of the hypopharynx-esophageal introitus is a rare occurrence. Surgical treatment was performed in the few cases reported in the literature. Endoscopic submucosal dissection (ESD) is a minimally invasive treatment for hypopharyngeal and esophageal lesions. Our objective was to evaluate the feasibility, safety, and efficacy of ESD for treatment of angiolipoma at the hypopharynx-esophageal introitus. The patients with submucosal tumors at the hypopharynx-esophageal introitus were diagnosed as angiolipoma by preoperative evaluation with endoscopy, endoscopic ultrasonography, and computed tomography (CT). The patients who were diagnosed with angiolipoma agreed to undergo endoscopic submucosal dissection. Under general anesthesia and endotracheal intubation, ESD was used to remove the lesions. Preoperative, intraoperative, and postoperative data were collected and analyzed to evaluate the feasibility, safety, and effectiveness of endoscopic submucosal dissection. From January 2013 to December 2018, 6 cases of angiolipoma were treated with ESD with a success rate of 100%. The average operation time was 107.0 ± 69.4 minutes. Intraoperative blood loss is the main risk. Endoscopic thermocoagulation successfully stopped bleeding in all cases. Pharyngeal pain and painful swallowing were the main clinical signs. There was no stricture at the hypopharynx-esophageal introitus after the operation. ESD treatment of angiolipoma at hypopharynx-esophageal introitus is feasible, safe, and effective.